Hyperhomocysteinaemia in children receiving phenytoin and carbamazepine monotherapy: a cross-sectional observational study. Issue 4 (7th November 2016) - Chandrasekaran, Saravanan; Patil, Sooraj; Suthar, Renu; Attri, Savita Verma; Sahu, Jitendra Kumar; Sankhyan, Naveen; Tageja, Mini; Singhi, Pratibha
Abstract : Objective: Long-term therapy with phenytoin and carbamazepine is known to cause hyperhomocysteinaemia. We evaluated the prevalence of hyperhomocysteinaemia in North Indian children receiving phenytoin or carbamazepine monotherapy for >6 months duration and the effect of folic acid supplementation on plasma homocysteine. Methods: In this cross-sectional observational study we enrolled consecutive children aged 2–12 years with epilepsy who had received phenytoin or carbamazepine monotherapy for >6 months. Plasma total homocysteine, folic acid, vitamin B12 and antiepileptic drug concentrations were measured. Healthy age- and sex-matched controls were recruited. Children with homocysteine >10.4 µmol/L received folic acid supplementation for 1 month and homocysteine and folic acid concentrations were measured after 1 month follow-up. Results: A total of 112 children receiving antiepileptic monotherapy for >6 months were enrolled. Hyperhomocysteinaemia was present in 54 children (90%) receiving phenytoin, 45 children (90%) receiving carbamazepine therapy and 17 (34%) controls (p<0.05). Mean plasma homocysteine concentrations were significantly higher (18.9±10.2 vs 9.1±3 µmol/L) and serum folic acid concentrations (10.04±8.5 ng/ml vs 12.6±4.8 p<0.001) and vitamin B12 concentrations (365±155 pg/mL vs 474±332 pg/mL, p=0.02) were significantly lower in the study group compared with the control group. Duration of antiepileptic drug therapy correlated significantly with elevated homocysteine and reduced folic acid concentrations (p<0.05). Supplementation with folic acid for 1 month led to a reduction in plasma homocysteine concentrations in the study group (from 20.9±10.3 µmol/L to 14.2±8.2 µmol/L, p<0.05). Conclusions: Phenytoin or carbamazepine monotherapy for >6 months duration is associated with hyperhomocysteinaemia in 90% of North Indian children. Elevated homocysteine concentrations were normalised in these children with folic acid supplementation.